Adaptability of the threatened jaguarundi (Herpailurus yagouaroundi Schereber, 1777) to human-altered environments in San Luis Potosí, Mexico - Coronado Quibrera, Wendy Paola; Olmos Oropeza, Genaro; Bender, Louis C.; Rosas Rosas, Octavio César; Palacio Núñez, Jorge; Tarango Arámbula, Luis Antonio; Herrera Haro, José G. (Instituto de Ecología, A.C., 2019)
Persistence and recovery of rare species in developing regions with limited protected areas depends upon their adaptability to human-altered habitats. The jaguarundi (Herpailurus yagouaroundi) is classed as threatened in Mexico, and knowledge of its distribution and environmental correlates is necessary for informed recovery efforts. However, little is known of jaguarundi habitat or distribution in interior Mexico, including the state of San Luis Potosí (SLP). We conducted 96 semi-structured interviews around communities, ejidos, and ranches throughout SLP to obtain records of jaguarundi presence and identify environmental correlates and site attributes associated with its occurrence. We evaluated interviews using analytical criteria of credibility, and collected habitat information from 50 reliable occurrences from three of the four geographic regions of SLP. Compared to the SLP landscape, jaguarundi occurrences were located closer to water, closer to roads, at lower elevation, marginally closer to communities, and in areas with greater total edge, edge density, and number of landscape patches. Jaguarundi showed preference for mosaics of tropical forest, agricultural, grassland, and urban (i.e., any community) cover types. Relatively dense hiding or ambush cover was usually present at occurrence sites. Collectively, maximum entropy modeling and logistic regression modeling predicted similar and high likelihood of jaguarundi presence in regions characterized by mosaics of tropical forest, agriculture, grassland, or urban cover types <500 m in elevation and <2 km from roads. These mosaic landscapes tended to be relatively close to communities of moderate population densities and water, and typically support higher small prey densities than less fragmented areas. Jaguarundi were adaptable to at least light–moderate human-related disturbance, and may be benefitted by it because of increased edge and habitat mosaics.